A photochemical determination of luminescence efficiency of upconverting nanoparticles - Amouroux, Baptiste; Roux, Clément; Micheau, Jean-Claude; Gauffre, Fabienne; Coudret, Christophe (Beilstein Journal of Organic Chemistry, 2019)
Upconverting nanoparticles are a rising class of non-linear luminescent probes burgeoning since the beginning of the 2000’s, especially for their attractiveness in theranostics. However, the precise quantification of the light delivered remains a hot problem in order to estimate their impact on the biological medium. Sophisticated photophysical measurements under near infrared excitation have been developed only by few teams. Here, we present the first attempt towards a simple and cheap photochemical approach consisting of an actinometric characterization of the green emission of NaYF4:Yb,Er nanoparticles. Using the recently calibrated actinometer 1,2-bis(2,4-dimethyl-5-phenyl-3-thienyl)-3,3,4,4,5,5-hexafluoro-1-cyclopentene operating in the green region of the visible spectra, we propose a simple photochemical experiment to get an accurate estimation of the efficiency of these green-emitting “nanolamps”. The agreement of the collected data with the previous published results validates this approach.
Keywords: actinometry; diarylethene; lanthanide; photochemistry; upconverting nanoparticle

(untitled) - Zhou, J.; Liu, Q.; Feng, W.; Sun, Y.; Li, F. (Chem. Rev., 2015)

(untitled) - Dong, H.; Du, S.-R.; Zheng, X.-Y.; Lyu, G.-M.; Sun, L.-D.; Li, L.-D.; Zhang, P.-Z.; Zhang, C.; Yan, C.-H. (Chem. Rev., 2015)

(untitled) - Himmelstoß, S. F.; Hirsch, T. (Methods Appl. Fluoresc., 2019)

(untitled) - Wu, S.; Han, G.; Milliron, D. J.; Aloni, S.; Altoe, V.; Talapin, D. V.; Cohen, B. E.; Schuck, P. J. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Lederhose, P.; Chen, Z.; Müller, R.; Blinco, J. P.; Wu, S.; Barner-Kowollik, C. (Angew. Chem., Int. Ed., 2016)

(untitled) - Wu, S.; Butt, H.-J. (Phys. Chem. Chem. Phys., 2017)

(untitled) - He, S.; Krippes, K.; Ritz, S.; Chen, Z.; Best, A.; Butt, H.-J.; Mailänder, V.; Wu, S. (Chem. Commun., 2015)

(untitled) - Xie, Z.; Deng, X.; Liu, B.; Huang, S.; Ma, P.; Hou, Z.; Cheng, Z.; Lin, J.; Luan, S. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Yan, B.; Boyer, J.-C.; Branda, N. R.; Zhao, Y. (J. Am. Chem. Soc., 2011)

(untitled) - Yan, B.; Boyer, J.-C.; Habault, D.; Branda, N. R.; Zhao, Y. (J. Am. Chem. Soc., 2012)

(untitled) - Fedoryshin, L. L.; Tavares, A. J.; Petryayeva, E.; Doughan, S.; Krull, U. J. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Cui, S.; Yin, D.; Chen, Y.; Di, Y.; Chen, H.; Ma, Y.; Achilefu, S.; Gu, Y. (ACS Nano, 2013)

(untitled) - Chen, S.; Weitemier, A. Z.; Zeng, X.; He, L.; Wang, X.; Tao, Y.; Huang, A. J. Y.; Hashimotodani, Y.; Kano, M.; Iwasaki, H.; Parajuli, L. K.; Okabe, S.; et al. (Science, 2018)

(untitled) - Wang, Y.; Lin, X.; Chen, X.; Chen, X.; Xu, Z.; Zhang, W.; Liao, Q.; Duan, X.; Wang, X.; Liu, M.; Wang, F.; He, J.; et al. (Biomaterials, 2017)

(untitled) - Auzel, F. (Chem. Rev., 2004)

(untitled) - Balabhadra, S.; Debasu, M. L.; Brites, C. D. S.; Ferreira, R. A. S.; Carlos, L. D. (J. Lumin., 2017)

(untitled) - Boyer, J.-C.; van Veggel, F. C. J. M. (Nanoscale, 2010)

(untitled) - May, P. S.; Baride, A.; Hossan, M. Y.; Berry, M. (Nanoscale, 2018)

(untitled) - Kaiser, M.; Würth, C.; Kraft, M.; Hyppänen, I.; Soukka, T.; Resch-Genger, U. (Nanoscale, 2017)

(untitled) - Nadort, A.; Sreenivasan, V. K. A.; Song, Z.; Grebenik, E. A.; Nechaev, A. V.; Semchishen, V. A.; Panchenko, V. Y.; Zvyagin, A. V. (PLoS One, 2013)

(untitled) - Amouroux, B.; Roux, C.; Marty, J.-D.; Pasturel, M.; Bouchet, A.; Sliwa, M.; Leroux, O.; Gauffre, F.; Coudret, C. (Inorg. Chem., 2019)

(untitled) - Kuhn, H. J.; Braslavsky, S. E.; Schmidt, R. (Pure Appl. Chem., 2004)

(untitled) - Aillet, T.; Loubiere, K.; Dechy-Cabaret, O.; Prat, L. (Int. J. Chem. React. Eng., 2014)

(untitled) - El Achi, N.; Bakkour, Y.; Chausset-Boissarie, L.; Penhoat, M.; Rolando, C. (RSC Adv., 2017)

(untitled) - Roibu, A.; Fransen, S.; Leblebici, M. E.; Meir, G.; Van Gerven, T.; Kuhn, S. (Sci. Rep., 2018)

(untitled) - Sumi, T.; Takagi, Y.; Yagi, A.; Morimoto, M.; Irie, M. (Chem. Commun., 2014)

(untitled) - Gurke, J.; Budzák, Š.; Schmidt, B. M.; Jacquemin, D.; Hecht, S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Carling, C.-J.; Boyer, J.-C.; Branda, N. R. (J. Am. Chem. Soc., 2009)

(untitled) - Li, Z.; Zhang, Y. (Nanotechnology, 2008)

(untitled) - Zhai, X.; Wang, Y.; Liu, X.; Liu, S.; Lei, P.; Yao, S.; Song, S.; Zhou, L.; Feng, J.; Zhang, H. (ChemPhotoChem, 2017)

Organic Photochromic and Thermochromic Compounds - Deniel, M. H.; Lavabre, D.; Micheau, J. C. (Photokinetics under Continuous Irradiation)

(untitled) - Conrad, R. H. (Anal. Chem. (Washington, DC, U. S.), 1967)

(untitled) - Kraft, M.; Würth, C.; Muhr, V.; Hirsch, T.; Resch-Genger, U. (Nano Res., 2018)

(untitled) - Khaydukov, E. V.; Mironova, K. E.; Semchishen, V. A.; Generalova, A. N.; Nechaev, A. V.; Khochenkov, D. A.; Stepanova, E. V.; Lebedev, O. I.; Zvyagin, A. V.; Deyev, S. M.; Panchenko, V. Ya. (Sci. Rep., 2016)

(untitled) - Irie, M.; Fukaminato, T.; Matsuda, K.; Kobatake, S. (Chem. Rev., 2014)

Luminescent and Photoactive Transition Metal Complexes as Biomolecular Probes and Cellular Reagents - Filevich, O.; Zayat, L.; Baraldo, L. M.; Etchenique, R. (Long Wavelength Phototriggering: Ruthenium-Based Caged Compounds, 2014)